Habilidades sociais em adolescentes : relações com dependência de internet e bullying - Terroso, Lauren Bulcão (2013)
The Social Skills have an important role in the social, academic and emotional development of adolescents. At this stage of life, to have a good repertoire of SS is associated with a healthy development, and the deficit of these behaviors is associated with numerous negative outcomes. Among the consequences associated with a poor repertoire of SS among young we highlight the internet addiction (IA) and the involvement in bullying behaviors. Given the above, the aim of this study was to verify, through two empirical studies the association between SS and IA, and between SS and bullying in a sample of adolescent students, residents in a city in the interior of Rio Grande do Sul state, Brazil. Both studies were quantitative and with a cross-sectional design. We used the following instruments: Inventário de Habilidades Sociais para Adolescentes(IHSA), Internet Addiction Test (IAT) and the Questionário Multimodal de Interação Escolar (CMIE-IV). Through the application of the instruments we sought to observe whether having IA and being involved in bullying behaviors were associated with lower scores of SS. We also tried to estimate which classes of social skills behaviors were associated with IA and bullying. As regarding the association between SS and IA, the results have indicated that IA was associated with greater difficulty in expressing social skills behaviors. Concerning the association between HS and bullying, it was possible to verify that either be victim or aggressor was associated with a lower repertoire of SS in the most of the factors of this construct. However, the results indicated that a lower repertoire of SS in adolescents was associated with having IA and being involved in bullying behaviors.